2009
DOI: 10.1197/jamia.m2559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Pharmacist-to-Dose Computerized Request on Promptness of Antimicrobial Therapy

Abstract: Pharmacists completed pharmacist-to-dose consultations for dosing guidance of vancomycin and aminoglycosides within a median of 30 minutes. Implementation of a computerized request for clinical pharmacists to provide medication-related clinical decision support increased medication turn-around time of vancomycin and aminoglycosides and reduced medication errors. Consultation of clinical pharmacists by computerized request for initial antibiotic dosing of medications with narrow therapeutic windows is an option… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…Most evidence came from specialty settings (such as intensive care, emergency medicine and paediatrics); and from high‐risk patient groups (e.g. those at risk for or with infections); and from tertiary care …”
Section: Resultsmentioning
confidence: 99%
“…Most evidence came from specialty settings (such as intensive care, emergency medicine and paediatrics); and from high‐risk patient groups (e.g. those at risk for or with infections); and from tertiary care …”
Section: Resultsmentioning
confidence: 99%
“…Antibacterial agents targeting unrelated bacterial functions or processes may synergistically enhance their bioactivity when used in combination, and the clinical application of combinatorial therapy is very common in the treatment antibiotic resistant bacterial infections . As plant‐derived triterpenoids target the cell membrane, these compounds may be suitable for synergistic combination with antibiotics that target intracellular processes.…”
Section: Resultsmentioning
confidence: 99%
“…Vincent and colleagues in a 2009 study, found that the median time for pharmacists to complete a pharmacist-to-dose order for aminoglycosides with an automated pharmacist alert system was 29 minutes. [9] Much of this time is spent collecting information that can be provided at the time of ordering by a laboratory system linked to CPOE. According to the pharmacists on the therapeutic drug monitoring surveillance team, the implementation of the aminoglycoside advisor reduced the amount of time spent adjusting initial aminoglycoside regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Although we were unable to quantify this change in resource use, we can estimate 30 minutes per order based on previously published data. [9]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation